C3 POLYMORPHISM IN LYMPHOSARCOMA AND HODGKIN DISEASE - D.D. Farhud (Tehran University of Medical Sciences, 1988)
The C3 phenotypes were determined by high-voltage agarose gel electrophoreses in German patients suffering from Lymphosarcoma (n=34), Hodgkin (n=59) and a group of other haematological diseases (n=46). Frequencies of C3 SS, SF and FF pho=enotypes were not significantly different from the frequencies found in a control group of 322 healthy Germans. However, high frequency of the FF phenotype in the three patient groups and low F gene frequency in Lymphosarcoma were found.